(untitled) (Marketing Journal, 2025)
The article examines Uzbekistan’s tourism development with a focus on the Zomin ecotourism zone. It analyzes recent reforms, infrastructure improvements, and policy measures aimed at increasing tourist inflow and economic diversification. The study applies SWOT and trend analysis to assess achievements and challenges, proposing recommendations to enhance tourism sustainability and competitiveness.